Does the sesamoid rotation angle change differently in subjects with hallux valgus considering foot position during assumed walking? A pilot study. (May 2022) - Hirota, Arisu; Maeda, Noriaki; Sakai, Shogo; Morikawa, Masanori; Kobayashi, Takumi; Shimizu, Reia; Kotoshiba, Somu; Sasadai, Junpei; Tashiro, Tsubasa; Urabe, Yukio
Highlights: The sesamoid rotation angle (SRA) of all positions and the change in the SRA at the pre-swing increased in the Hallux valgus (HV) group than in the non-HV group. No statistically significant difference between the two groups with respect to cross-sectional area of the abductor hallucis muscle (ABH) in this study. In the HV group, larger change in the SRA during load on forefoot is associated with smaller size of ABH. Abstract: Hallux valgus (HV) entails changes in the alignment of the rotating sesamoids and a shift of the abductor hallucis muscle (ABH) in the plantar direction, decreasing the abductor force. Load on the foot while walking may change the sesamoid rotation angle (SRA). Nevertheless, no study has investigated the relationship between the change in SRA during assumed walking and ABH muscle size. The aim of our study was to examine the changes in SRA at different foot postures assumed to generate skeletal alignments during walking and muscle size of the ABH in participants with HV and to discuss the association between the change in the SRA and cross-sectional area (CSA) of the ABH. Thirteen female participants were recruited and divided into the HV and non-HV groups according to the HV angle. The SRA and cross-sectional area of the ABH were measured using B-mode ultrasound. The SRA was measured under four conditions; sitting, standing, mid-stance, and pre-swing posture. The CSA was assessed in the supine position. In all postures, the SRA increased more in the HV group than in the non-HV group (p < 0.05). The change in the SRA at the pre-swing posture was greater in the HV group than in the non-HV group (p < 0.05). The change in the SRA at pre-swing posture negatively correlated with the CSA of the ABH in the HV group (r = −0.554, p < 0.05). In the HV group, increasing the load on the forefoot enhanced the sesamoid rotation. Abductor torque on the ABH decreased with ABH displacement as the sesamoids moved laterally in the pre-swing. Repeated walking increased sesamoid rotation and led to HV progression. Therefore, it may be beneficial to use an orthosis or arch pad that corrects pronation of the metatarsal with the rotation of the sesamoids.